Management of Spinal Hemangioblastoma in Von Hippel-Lindau Disease: A Case Report - Hooshang Saberi; Arad Iranmehr; Nazi Derakhshanrad; Abolfazl Payinmahalli; Vahid Soleimani (Acta Medica Iranica, 2023)
Vertebral body location of hemangioblastomas (HB) is extremely rare. The authors report a case of spinal mass involving lower thoracic region with cord compression, approved to be spinal HB. A 57-year-old man presented to our center with eight months history of progressive intractable back pain and paraparesis. Admission computed tomography and magnetic resonance imaging (MRI) of the thoracolumbar spine demonstrated a lytic and expansile spinal mass with pedicle expansion and vivid contrast enhancement involving T11 and T12 vertebral bodies on the right side. He was a known case of von Hippel-Lindau (VHL) and he had history of 4th ventricular asymptomatic hemangioblastoma near Obex, multiple pancreatic cystic adenomas, multiple liver cysts, and right non-chromaffin adrenal mass. The patient underwent a T11-T12 partial transpedicular corpectomy with T5 to L3 posterior spinal fixation to bridge the invaded segment. The pathological and immunohistochemical findings were consistent with vertebral HB. Spinal HB although extremely rare, may be managed with subtotal tumor resection and fixation of normal adjacent vertebrae by cemented screws.